Overview of The Incidence of Hyperprolactinemia Side Effects in Schizophrenia Patients With Antipsychotic Therapy - Vivinia RA Putri; Dita Hasni; Nadia Purnama Dewi; Mutiara Anissa (Universitas Muhammadiyah Sumatera Utara, 2020)
Antipsychotic-induced hyperprolactinemia disorder affects the morbidity and quality of life of the patient, and can lower the patient's adherence to taking antipsychotics, thereby lowering the therapeutic success rate. This study aims to figure out the incidence of hyperprolactinemia side effects in schizophrenia patients receiving antipsychotic therapy. This descriptive research was conducted at HB Saanin Psychiatric Hospital Padang in January-June 2018. The population in this study is all schizophrenia patients in the HB. Saanin Psychiatric Hospital Padang Year 2018 and involved participants as many as 100 people recruited in consecutive sampling. Data were analyzed using a descriptive statistical method. The results showed that more than half of the patients were 59 people (59.0%) hyperprolactinemia. Patients with gynecomastia amounted to 16 people (16%). Patients with galactorrhea amounted to 3 people (3%). Patients with sexual dysfunction amounted to 19 people (19%). Male patients amounted to 60 people, 21 people (35%) The sexual dysfunction of female patients amounted to 40 people, 26 people (65%) Menstrual cycle changes. More than half of the Schizophrenia patients receiving antipsychotic therapy in this study suffer symptoms of hyperprolactinemia in the manifestation of galactorrhea, gynecomastia, menstrual disorders, and sexual dysfunction.